Pengembangan Budaya Religius di SMP Negeri 10 Palembang - Febriyanti, Febriyanti; Rusmaini, Rusmaini (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2020)
The religious culture of educational institutions is an effort to realize the values ​​of religious teachings as a tradition in behavior and organizational culture which is followed by all citizens in the educational institution. The research approach is qualitative field with case studies. Types of data are qualitative and quantitative. Sources of data are primary data and secondary data. Data collection techniques use observation, interviews, and documents, while data analysis refers to Miles and Huberman's theory. The results of the study obtained 4 conclusions, namely: The first stage, planning a religious culture development program is the formulation of a vision, mission, and goals in State Junior High School 10 Palembang connected with religious culture clearly. The second stage is the implementation of programs that are obligatory for all school members. The final stage, evaluating the program of religious cultural values ​​in instilling character education is in the five character values ​​and 4S (smile, greeting, greeting, and courtesy). The five religious cultural values ​​are honest in words, clean in deeds, economical in use, sincere in giving to fellow brothers and sisters, in congregation (mutual cooperation or cooperation). The evaluation of the results of the development of religious culture is included in the chasing achievement book which contains the activity form or student attendance that will be assessed by each supervisor. Supporting factors for the development of religious culture, namely students, teachers, infrastructure, literacy activities. Meanwhile, the inhibiting factor is fanaticism, the lack of awareness of some teachers who consider it the only task of Islamic Education teachers.